The study of nadir fruits as stamp design subject matter, in the context of tourism promotion / Nuraini Huda Mohd Fairuz - Mohd Fairuz, Nuraini Huda (2018)
Fruits are one of the high value economies for money in the country. Malaysia is a very lucky country with good and fertile land for agriculture. Therefore, it is rich in diversity of genetic resources, especially fruits. The fruit in Malaysia can be categorized into two types, namely, Main fruits and Nadir fruits. Commonly known and commercially renowned fruits are the most important fruits, such as local fruits. Nadir fruits is a fruit that is hard to find and is rarely grown commercially. It is rarely found and served as a dish and is further marginalized. This is because it can only be found in isolated villages or in certain states such as Melaka. On the contrary, many people who do not know what a rare fruit is and do not know more about these rare fruits. This rare fruit has its secret and its own uniqueness. Various conservation and preservation activities must be carried out to maintain awareness of the importance of the fruits. In conclusion, this study was carried out in order to market fruits even more, turning fruits into one of the tourist destinations in Malaysia.